Retrieving parameters of agile cities: A systematic literature review - Salma Anwar; Abeer Elshater; Samy Afifi; Ayat Ismail; Hebatullah Ghalib (Ain Shams Engineering Journal)
This study addresses the challenge of creating agile, adaptable urban environments in the Global South, utilizing technology, innovation, and sustainability to respond to evolving challenges. Through a systematic review and content analysis of materials sourced from multiple databases, the research develops a replicable framework for cities to achieve agility. Key findings provide adaptive guiding parameters for agile cities and define the ‘agile city’ concept, filling a significant gap in the literature. Findings conclude that in urban planning, ‘agility’ signifies the quickness and effectiveness of cities’ adaptation to dynamic conditions via flexible infrastructure, innovative governance, and data-driven decision-making. The findings also retrieve ‘agile city,’ with a comprehensive approach that integrates these elements to achieve resilience, adaptability, and sustainability. By proposing new guiding parameters, this research illustrates pathways for cities to enhance agility across various domains, supporting urban planners and policymakers in advancing flexible, responsive urban environments.